The TRANSIENT ANALYSIS OF A. D. C. MOTOR FED FROM STATIC CONVERTER - Nasir, Bilal; M.S. M. AL. Ani (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
Separately excited D.C. motors are widely uses for precision control of position, Speed and torque output. One of the common mode is to use fixed field excitation and variable armature voltage which fed from 3- phase bridge fully controlled convertor. Computer program  for the system analysis been carried out to study the behavior of the motor during the transient periods. Good agreement has been obtained between experimental and computed results for transient conditions